The physical actor : contact improvisation from studio to stage - Loui, Annie (Routledge, 2019)
"The Physical Actor is a comprehensive book of exercises for actors. It is carefully designed for the development of a strong and flexible physical body able to move with ease through space and interact instinctively on-stage. Annie Loui draws on her training with Etienne Decroux, Carolyn Carlson, and Jerzy Grotowski to bring Contact Improvisation into the theatrical sphere. She explains how it can be used to develop alert and embodied listening skills in the actor, and how to apply it to working with texts on stage. This book will guide the reader through a full course of movement skills, including: - Partnering skills - Spatial awareness for groups and individuals - Fine motor control through mime - Heightened co-ordination and sustained motion New for this edition are additional partnering exercises, in-depth applications of contact improvisation to monologues and scenes, and a chapter on devising physical theatre performances"--